2018
DOI: 10.1021/acscatal.8b01710
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Oxophilicity in Copper-Catalyzed Water Dissociation

Abstract: Understanding water dissociation on nonprecious metal surfaces is essential toward designing efficient catalysts for important chemical reactions such as water-splitting and carbon dioxide reduction. Hydrogen binding energy (HBE) has been proposed to be a good descriptor to predict hydrogen evolution reaction (HER) activity in alkaline electrolytes. In this work, we showed that although HBE values could predict the HER activity reasonably well, the oxophilicity of the catalyst surface also played a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 33 publications
1
51
0
1
Order By: Relevance
“…Taking these energies as an input of the kinetic model, we predict the current density as shown in the Supplementary Figure 15, from which we estimated an overpotential of HER of ~0.4 V, consistent with the experiment. 6 Supplementary Figure 15: The current density of HER predicted from the kinetic model. 7…”
Section: Prediction Of Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…Taking these energies as an input of the kinetic model, we predict the current density as shown in the Supplementary Figure 15, from which we estimated an overpotential of HER of ~0.4 V, consistent with the experiment. 6 Supplementary Figure 15: The current density of HER predicted from the kinetic model. 7…”
Section: Prediction Of Hydrogen Evolution Reaction (Her)mentioning
confidence: 99%
“…Introducing oxophilic metal elements to tailoring the adsorption energy of the OH ad intermediate thus modulating the kinetics of the Volmer step while preserving the high activity of hosts towards the Tafel or Heyrovsky step are more common strategies to boost the alkaline HER performance. [136] Kim et al calculated the change of the OH ad binding energies after incorporating a series of exophilic transition metal elements onto the metallic Ni surface. [129] The calculation model was shown in Figure 13e.…”
Section: Synergistic Guest-host Interaction For Hydrogen Evolution Reactionmentioning
confidence: 99%
“…[ 6 ] Very recently, it was reported that HER activity of copper was significantly enhanced via doping with small amounts of oxophilic transition metals. [ 7 ] The promoted HER performance was mainly ascribed to the interaction between oxophilic component and oxygen atom of water molecule. Meanwhile, Kim et al.…”
Section: Introductionmentioning
confidence: 99%